Dimensi Kosmologis Ritual Rokat Pandhaba pada Masyarakat Madura - Badrul Munir Chair (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2020)
Rokat pandhaba is an exorcism ritual for child who has certain advantages or abilities caused by the arrangement of their birth in a family. Performing rokat pandhaba carries the hope that all the bad traits and possible harms to the child can be eliminated. This study attempted to explore the cosmological dimensions in the rokat pandhaba ritual carried out by the Madurese community. This is a qualitative research with metaphysical cosmological approach. The data were collected through indepth interviews, observations, and documentation and analyzed by using the interpretation theory of symbols and elements as found in rokat pandhaba ritual. The results of this study indicated that the rokat pandhaba ritual held by Madurese contains symbols that have implied meanings related to their concept of birth and the relationship between humans and the cosmos. The human life, especially their fate and fortune depends on how they treat the nature. It also has the conception that Madurese people are very accepting of metaphysical force and believe that it affects on human life in earth